Structural Characterization of a Rhamnogalacturonan I Domain from Ginseng and Its Inhibitory Effect on Galectin-3 - Shi, Huimin (Molecules, 2017)
A rhamnogalacturonan I domain, named RG-I-3A, was prepared from ginseng pectin by pectinase digestion and chromatography separation. Monosaccharide composition analysis revealed that it was mainly composed of galacturonic acid, rhamnose, galactose, and arabinose in a molar ratio of 32.5:11.2:31.9:16.5, with a molecular weight of 50 kDa. Partial acid hydrolysis, monoclonal antibody detection, and NMR spectra analysis suggested RG-I-3A was composed of →4)-α-GalpA-(1→2)-α-Rhap-(1→disaccharide repeating units as backbone, with β-1,4-galactan, α-1,5-arabinan, AG-I, and AG-II side chains substituted via the O-4 of Rhap. Galectin-3-mediated hemagglutination and biolayer interferometry assay indicated that RG-I-3A had inhibitory activity on galectin-3. These findings suggest the potential use of this ginseng RG-I domain as a galectin-3 inhibitor in drug development applications.